1981
DOI: 10.1111/j.1365-2125.1981.tb01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, bioavailability and ECG response of verapamil in patients with liver cirrhosis.

Abstract: 1 The pharmacokinetics, bioavailability and ECG response of verapamil was investigated in seven patients with liver cirrhosis and compared with six normal subjects, using stable labelled techniques whereby both the intravenous and oral dose are given simultaneously. 2 After intravenous administration, plasma concentrations were much higher in the patient group such that the total plasma clearance was reduced from a mean of 1258 ml/min in normals to 616 ml/min in the patient group (P less than 0.0025). The appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…There Eichelbaum et al, 1980Eichelbaum et al, , 1981Eichelbaum et al, a,b, 1984McAllister & Kirsten 1982). Previous studies have demonstrated that the same concentration of plasma verapamil following oral administration appeared to be two to three times less potent than that following i.v.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There Eichelbaum et al, 1980Eichelbaum et al, , 1981Eichelbaum et al, a,b, 1984McAllister & Kirsten 1982). Previous studies have demonstrated that the same concentration of plasma verapamil following oral administration appeared to be two to three times less potent than that following i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Somogyi et al (1982) proposed an equation to predict F of highly cleared drugs with reasonable accuracy. Since their original equation for verapamil was obtained from a limited number of subjects (n = 6), we added the present data as well as those obtained from patients with liver cirrhosis (Somogyi et al, 1981) In a recent study we demonstrated that the volume of distribution for the (-)-isomer was two times greater than that of the (+)-isomer . Therefore, the plasma concentration of the (+)-isomer was two times higher than that of the (-)-isomer following i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He was ventilated, and haemofiltered because of acidosis and a rising serum creatinine (maximum 424 g1M). His cardiac output was 8.6 1 min -1 (reference range 4-8), pulmonary capillary wedge pressure 21 mm Hg (6)(7)(8)(9)(10)(11)(12), and systemic vascular resistance 456 dyn s-1 m-2 (800-1200). He required dopamine, noradrenaline, and adrenaline to maintain systolic pressure.…”
Section: Case Reportmentioning
confidence: 99%
“…Thus hepatic failure or decreased hepatic blood flow due to cardiac failure slows the metabolism of CCB. 21 The elimination of the inactivated compounds takes place mainly in the kidneys. However, chronic treatment prolongs the half-life because of saturation of hepatic first-pass effect, i.e., verapamil elimination half-life is extended to 6-9 hr.…”
Section: Mechanism Of Actionmentioning
confidence: 99%